EXQ Gas Enterprise : cooking gas delivery/ Mohd Asraf Mohd Aduros... [et al.] - Mohd Aduros, Mohd Asraf; Abdullah, Azizul; Abdullah, Mohd Nazri; Edrus, Mohamad Asyraf (2007)
EXQ Gas Enterprise exists in the world of business retailing providing excellent service and products towards our customers officially. We are selling gas cylinder from Petronas for cooking. This product has stable demand and is continuing to grow bit by bit. We also act as distributor in the particular area as we only focus on one product. We will supply to housing area, restaurant and local convenience store.